Answer:
See explanation
Step-by-step explanation:
1. Factor the function ![f(x)=-2x^2+16x-30:](https://tex.z-dn.net/?f=f%28x%29%3D-2x%5E2%2B16x-30%3A)
![f(x)=-2x^2+16x-30=-2x^2+6x+10x-30=-2x(x-3)+10(x-3)=-2(x-3)(x-5).](https://tex.z-dn.net/?f=f%28x%29%3D-2x%5E2%2B16x-30%3D-2x%5E2%2B6x%2B10x-30%3D-2x%28x-3%29%2B10%28x-3%29%3D-2%28x-3%29%28x-5%29.)
2. The zeros (or the solutions of the equation f(x)=0) are x=3 and x=5. So? points (3,0) and (5,0) are the points on the graph that are the solutions of the equation.
3. Find the vertex:
![x_v=-\dfrac{b}{2a}=-\dfrac{16}{2\cdot (-2)}=4,\\ \\y_v=-2\cdot 4^2+16\cdot 4-30=-32+64-30=2.](https://tex.z-dn.net/?f=x_v%3D-%5Cdfrac%7Bb%7D%7B2a%7D%3D-%5Cdfrac%7B16%7D%7B2%5Ccdot%20%28-2%29%7D%3D4%2C%5C%5C%20%5C%5Cy_v%3D-2%5Ccdot%204%5E2%2B16%5Ccdot%204-30%3D-32%2B64-30%3D2.)
Thus, the coordinates of the vertex are (4,2) and the axis of symmetry is the vertical line that passes trough the vertex: x=4.
Answer:
you multiply all of those answers
Step-by-step explanation:
3.057.02 is your answer to this question.
<span>2x^2 − 2z^4 + y^2 − x^2 + z^4
</span>2(-4)^2 − 2(2)^4 + (3)^2 − (-4)^2 + (2)^4
2(16) - 2(16) + 9 - 16 + 16
32 - 32 + 9 - 16 + 16
answer is 9